2017
DOI: 10.1016/j.jiph.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Are Saudi medical students aware of middle east respiratory syndrome coronavirus during an outbreak?

Abstract: Recently, an outbreak of MERS-CoV occurred in King Abdulaziz Medical City (KAMC), Riyadh. This outbreak contributed to the students at the King Saud bin Abdulaziz University for Health Sciences (KSAU-HS) becoming more involved in promoting health awareness in their communities. This was a cross-sectional study that evaluated students in the clinical phase of medical school. The data were collected by an online questionnaire. The measurements were obtained using a researcher-administered and a self-reported que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 15 publications
7
36
1
Order By: Relevance
“…This implies that higher education gave the health practitioners credence in themselves in that they can carry out preventive measures and deliver quality care to patients. This finding is in agreement with the study of Al-Mohrej and Agha [28] which demonstrated that more educated individual scored significantly higher than others when it comes to MERS-CoV awareness. It has been reported that a good explanation for a low level of efficacy/self-efficacy and desire to carry out the preventive measures regarding MERS-CoV infection is that the participants were health practitioners with no previous experience or exposure to such cases.…”
Section: Relationship Of Demographic Profiles Tosupporting
confidence: 92%
“…This implies that higher education gave the health practitioners credence in themselves in that they can carry out preventive measures and deliver quality care to patients. This finding is in agreement with the study of Al-Mohrej and Agha [28] which demonstrated that more educated individual scored significantly higher than others when it comes to MERS-CoV awareness. It has been reported that a good explanation for a low level of efficacy/self-efficacy and desire to carry out the preventive measures regarding MERS-CoV infection is that the participants were health practitioners with no previous experience or exposure to such cases.…”
Section: Relationship Of Demographic Profiles Tosupporting
confidence: 92%
“…Prior studies in the central, east and west areas of Saudi Arabia investigated the awareness regarding MERS. [9][10][11][12] For the first time in Najran area and even in the south west of Saudi Arabia, the present study attempted to assess knowledge about this disease.…”
Section: Discussionmentioning
confidence: 99%
“…A structured questionnaire was developed by the researcher with the help of existing literature. 11,13 Out of 1162 health colleges' students registered in five health colleges, 418 participated in this study with percent of 35.9%. The number of registered students varies between the colleges, therefore different number of students participated from each college in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations